Real-Time Generative AI in Game Texture Rendering : A Systematic Analysis of Visual Enhancement Technologies - Avtar Singh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the integration of generative artificial intelligence (GAI) integration in real-time 3D texture rendering for modern gaming applications, presenting theoretical frameworks and practical implementations. Through a comprehensive analysis of current implementations across multiple game development platforms, the article demonstrates how GAI algorithms can dynamically generate and modify high-fidelity textures during gameplay, resulting in a 47% reduction in manual texture creation time and a 32% improvement in runtime performance compared to traditional methods. The article employs a mixed-methods approach, combining quantitative performance metrics with a qualitative assessment of visual quality and player immersion across 150 procedurally generated environments. The article findings indicate that GAI-driven texture rendering streamlines the development pipeline and enables advanced features such as context-aware texture adaptation and dynamic environmental response systems. Furthermore, the results suggest that this technology significantly enhances player immersion, with 85% of test subjects reporting improved visual consistency and environmental reactivity. This article contributes to the growing body of knowledge in real-time rendering optimization. It provides a foundation for future developments in automated game asset generation while also addressing critical challenges in processing overhead and quality consistency management.